Clinical and serological predictors of relapse in pemphigus: a study of 143 patients. (27th August 2021) - Genovese, G.; Maronese, C. A.; Casazza, G.; Corti, L.; Venegoni, L.; Muratori, S.; Berti, E.; Fanoni, D.; Marzano, A. V.
Summary: Background: Pemphigus is an autoimmune bullous disease mediated by autoantibodies targeting epithelial cell–cell adhesion molecules. Predictors of relapse have not yet been clearly identified. Aims: To identify factors at diagnosis and during follow‐up that could be predictors of relapse. Methods: Clinical and immunopathological data at diagnosis, clinical remission and first relapse from patients with pemphigus vulgaris or foliaceus and at least a 36‐month follow‐up were collected retrospectively. Based on the autoantibody profile at diagnosis, three serological patient subsets were devised: (i) anti‐desmoglein (Dsg)1‐positive and anti‐Dsg3‐negative; (iii) anti‐Dsg1‐negative and anti‐Dsg3‐positive; and (iii) anti‐Dsg1‐positive and anti‐Dsg3‐positive. Results: Data from 143 patients were collected. No significant differences were found between relapsers ( n  = 90) and nonrelapsers ( n  = 53) for time to remission or for anti‐Dsg1 and anti‐Dsg3 titres at diagnosis and remission. In the analysis of all patients, a higher risk of relapse was found for a body surface area (BSA) score of 3 compared with BSA < 3 (OR = 3.30, 95% CI 1.17–9.28; P  = 0.02) and for a positive titre of either anti‐Dsg1 or anti‐Dsg3 autoantibodies at remission compared with both being negative (OR = 2.42, 95% CI 1.21–4.85, P  = 0.01). In patients who were anti‐Dsg3‐positive and anti‐Dsg1‐negative at diagnosis, failure to achieve anti‐Dsg3 negativity at clinical remission was a significant predictor of relapse (OR = 7.89, 95% CI 2.06–30.21; P  < 0.01). Similarly, failure to achieve anti‐Dsg1 negativity at clinical remission was a significant predictor of relapse in patients with both anti‐Dsg1 and anti‐Dsg3 positivity at diagnosis (OR = 5.74, 95% CI 1.15–28.61; P  = 0.03), but not in those who were anti‐Dsg1‐positive/anti‐Dsg3‐negative at diagnosis (OR = 1.08, 95% CI 0.27–4.30; P  = 0.91). Conclusion: Regardless of pemphigus subtype, autoantibody titre negativity at clinical remission in patients classified based on their anti‐Dsg1 and anti‐Dsg3 profile at diagnosis and BSA were useful tools in predicting relapse.